Controlling Multi-Drug-Resistant Traits of Salmonella Obtained from Retail Poultry Shops Using Metal–Organic Framework (MOF) as a Novel Technique - W. Kamal; Rehab Mahmoud; Abeer Enaiet Allah; Ahmed A. Farghali; Abdalla Abdelwahab; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Manar Bahaa El Din Mohamed; Sahar Abdel Aleem Abdel Aziz (Microorganisms, 2023)
Salmonella spp. is considered one of the most important causes of food-borne illness globally. Poultry and its products are usually incriminated in its spread. Treatment with antibiotics is the first choice to deal with such cases; however, multi-drug resistance and biofilm formation have been recorded in animals and humans. This study aimed to detect the antibiotic profile of isolated traits from different sources and to find innovative alternatives, such as MOFs. A total of 350 samples were collected from randomly selected retailed poultry shops in Beni-Suef Province, Egypt. Their antimicrobial susceptibility against eight different antibiotics was tested, and multi-drug resistance was found in most of them. Surprisingly, promising results toward MOF were detected. Cu/Ni/Co-MOF (MOF3) showed superior antibacterial efficiency to Cu/Ni-MOF (MOF2) and Cu-MOF (MOF1) at p value ≤ 0.01. These findings highlight the tendency of Salmonella spp. to develop MDR to most of the antibiotics used in the field and the need to find new alternatives to overcome it, as well as confirming the ability of the environment to act as a source of human and animal affection.